2008
DOI: 10.1111/j.1365-2826.2008.01734.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Immediate‐Early Gene Activation‐ c‐fos and Beyond

Abstract: Immediate‐early genes (IEG) are powerful tools for identifying activated neurosecretory neurones and extended circuits that affect neuroendocrine functions. The generally acknowledged scenario is when cells became activated, IEGs expressed and IEG‐encoded transcription factors affect target gene expression. However, there are several examples in which: (i) neuronal activation occurs without induction of IEGs; (ii) IEG induction is not related to challenge‐induced neuropeptide expression; and (iii) markers of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
295
1
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(326 citation statements)
references
References 102 publications
(112 reference statements)
9
295
1
16
Order By: Relevance
“…For c-fos induction, 30 min after initial exposure to either L/D or L/D + H, zebrafish were killed and their brains were processed for in situ hybridization and counterstained with nuclear fast red. A time frame of 30 min was chosen, based on many previous studies showing the highest expression of c-fos mRNA 30 min after behavioral induction of neuronal activities [reviewed in (41) and references therein]. Images were taken with a Zeiss compound microscope.…”
Section: Methodsmentioning
confidence: 99%
“…For c-fos induction, 30 min after initial exposure to either L/D or L/D + H, zebrafish were killed and their brains were processed for in situ hybridization and counterstained with nuclear fast red. A time frame of 30 min was chosen, based on many previous studies showing the highest expression of c-fos mRNA 30 min after behavioral induction of neuronal activities [reviewed in (41) and references therein]. Images were taken with a Zeiss compound microscope.…”
Section: Methodsmentioning
confidence: 99%
“…To address this issue, we used a cage that was divided into two compartments (large and small) by a mesh partition, and we examined the effects of intruder encounters on c-Fos expression and the levels of DA and 5-HT in the brains of resident mice reared in a group or in isolation. We used c-Fos expression to measure regional changes in brain activity (Koda et al, 2010;Kovács, 2008). As a control, we further examined female isolationreared mice, because they do not develop hyper-aggression, unlike male isolation-reared mice (Pinna et al, 2005(Pinna et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there has been a need to validate this method, and other immediate early gene products have been used to map stress responses; in many, but not all, of these studies there is considerable overlap in activated areas. 90,114 In the context of hours-long stress, we have previously examined pCREB activation 115 and found that although the distribution of activated cells was similar to that labeled by Fos, pCREB activation followed a rapid and transient time-course which is not optimal for the hours-long stress models employed here. More recently, the activity-regulated cytoskeletal-associated protein (Arc) has emerged as an alternative tool to examine activity-dependent transcription, with particular relevance for mechanisms of plasticity.…”
Section: Discussionmentioning
confidence: 95%
“…There are known limitations to this technique. 89,90,114 Most notably the fact that not all cell types express the gene product, and thus the absence of Fos does not necessarily mean a cell was not activated or involved in stress processing. Therefore, there has been a need to validate this method, and other immediate early gene products have been used to map stress responses; in many, but not all, of these studies there is considerable overlap in activated areas.…”
Section: Discussionmentioning
confidence: 99%